Evolution of DA white dwarfs in the context of a new theory of convection - Althaus, Leandro Gabriel (1998)
In this study we compute the structure and evolution of carbon-oxygen DA white dwarfs by means of a detailed and updated evolutionary code. We treat the energy transport by convection within the formalism of the full spectrum turbulence theory, as given by the Canuto, Goldman and Mazzitelli (CGM) model. We explore the effect of various hydrogen layer masses on both the surface gravity and the hydrogen burning. Convective mixing at low luminosities is also considered. One of our main interests in this work has been to study the evolution of ZZ Ceti models, with the aim of comparing the CGM and mixing length theory (MLT) predictions. In this connection, we find that the temperature profile given by the CGM model is markedly different from that of the ML1 and ML2 versions of MLT. We have also computed approximate effective temperatures for the theoretical blue edge of the DA instability strip by using thermal timescale arguments for our evolving models. In this context, we found that the CGM theory leads to blue edges that are cooler than the observed ones. However, because the determination of the atmospheric parameters of ZZ Ceti stars is dependent on the assumed convection description in model atmosphere calculation, observed blue edges computed considering the CGM theory are required in order to perform a sef consistent comparison of our results with observations. Finally, detailed pulsation calculations of ZZ Ceti models considering the CGM convection would be necessary to place the results found in this paper on a firmer basis.